PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS â€œPDEODEâ€ MATERI SISTEM PENCERNAAN MANUSIA (Journal of Biology Education, 2015)
Abstract The aims of this research are to develop student worksheet based on PDEODE teaching strategy and to measure the effectiveness of student worksheet for the learning outcome and student activity of human digestive system concept. This reaserch was research and development (R & D) with two field testing. Testing of product was VIII D class in Junior High School 1 Jakenan and the use of product was VIII B class in Junior High School 1 Jakenan and VIII A class in Junior High School 1 Winong. The use of product student worksheet using one group pretest-postest design. The result validation of specialist was 86,4% withvery reasonable criteria.The average of N-gain 0,64indicating that there was an increasing learning outcome from pretest to posttest with medium criteria.The average classical completeness of students reached 83,21% and the average percentage classical of student activity reached 72,05% with active criteria. Based on the results of research concluded that the development of student worksheet on the basis of PDEODE was reasonable and effective in learning outcome and student activity for learning of human digestive system concept. Abstrak Penelitian ini bertujuan untuk mengembangkan LKS berbasis PDEODE dan mengukur keefektifan LKS terhadap hasil belajar dan aktivitas siswa pada materi sistem pencernaan manusia. Rancangan penelitian ini adalah penelitian dan pengembangandengan dua uji coba lapangan. Uji coba produk dilaksanakan di SMP N 1 Jakenan kelas VIII D dan uji coba pemakaian dilaksanakan di SMP N 1 Jakenan kelas VIII B dan SMP N 1 Winong kelas VIII A. Uji coba pemakaian LKS menggunakan one group pretest-postest design. Hasil validasi ahli sebesar 86,4% dengan kriteria sangat layak. Rata-rata nilai N-gain sebesar 0,64 menunjukkan adanya peningkatan hasil belajar dari pretest ke posttest dengan kriteria sedang. Rata-rata ketuntasan klasikal mencapai 83,21% dan rata-rata persentase aktivitas siswa secara klasikal mencapai 72,05% dengan kriteria aktif. Berdasarkan hasil penelitian dapat disimpulkan bahwa pengembangan LKS berbasis PDEODE layak dan efektif terhadap hasil belajar dan meningkatkan aktivitas siswa dalam pembelajaran sistem pencernaan manusia. Â  Â